2011
DOI: 10.1158/1940-6207.capr-10-0025
|View full text |Cite
|
Sign up to set email alerts
|

A Migration Signature and Plasma Biomarker Panel for Pancreatic Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma is a disease of extremely poor prognosis for which there are no reliable markers of asymptomatic disease. To identify pancreatic cancer biomarkers, we focused on a genomic interval proximal to the most common fragile site in the human genome, chromosome 3p12, which undergoes smoking-related breakage, loss of heterozygosity, and homozygous deletion as an early event in many epithelial tumors, including pancreatic cancers. Using a functional genomic approach, we identified a seve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Promising tumour markers derived from the PDAC tumour stroma, including matricellular proteins such as OPN, have previously been reported [24][25][26][27][28][29]. We have previously reported that collagen fragments derived from the basement membrane (BM) are elevated in PDAC patients at the time of diagnosis [28,29], and that type IV collagen has a role in PDAC cell survival and migration [20].…”
Section: Discussionmentioning
confidence: 99%
“…Promising tumour markers derived from the PDAC tumour stroma, including matricellular proteins such as OPN, have previously been reported [24][25][26][27][28][29]. We have previously reported that collagen fragments derived from the basement membrane (BM) are elevated in PDAC patients at the time of diagnosis [28,29], and that type IV collagen has a role in PDAC cell survival and migration [20].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, TN-C expression is correlated with disease progression and relapse by metastasis to the lung and is a potential biomarker for the disease (135, 136). Similarly, TN-C has also been noted as a biomarker for pancreatic, bladder, colorectal cancers, and glioma (137141). Therapeutic inhibition of TN-C is a possible treatment strategy in these models as well, which was illustrated in a mouse breast cancer model when cells treated with shRNA against TN-C produced fewer metastases (135).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, expression of key regulators might be expected to be elevated in invasive and metastatic cancer. MRCKa was identified in breast cancer as part of a gene expression signature linked to poor prognosis and increased incidence of metastasis under five years (7), and one of a seven gene panel with significantly elevated expression in pancreatic adenocarcinoma compared to normal pancreas (8). Invasiveness of MDA MB 231 breast cancer cells was inhibited by knockdown of either ROCK or MRCK kinases, but the most effective treatment was combined ROCK and MRCK knockdown or inhibition (9,10).…”
Section: Mrckmentioning
confidence: 99%